1986
DOI: 10.1163/22941932-90000431
|View full text |Cite
|
Sign up to set email alerts
|

Induction of Compression Wood in Rooted Cuttings of Pseudotsuga Menziesii (MIRB.) Franco by Indole-3-Acetic Acid

Abstract: A study was conducted to determine if exogenously applied indole-3-acetic acid would stimulate symmetric or asymmetric compression wood formation in stems of rooted cuttings of Pseudotsuga menziesii (Mirb.) Franco. Dormant two-year-old rooted cuttings were decapitated one cm below the terminal bud and treated with IAA in lanolin emulsion. Plants treated with IAA at 1 or 10 mg/g concentrations produced up to 25 rows of new xylem cells during the three week treatment period, while control plants produced essenti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
2

Year Published

1996
1996
2016
2016

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 4 publications
0
3
0
2
Order By: Relevance
“…Gravistimulation of primary roots and shoots resulting in differential growth responses and geotropism is mediated by auxin efflux regulators and a lateral transport of IAA toward the lower side in coleoptiles, shoots, and roots as demonstrated in maize coleoptiles, snapdragon, and Arabidopsis (Philippar et al, 1999;Philosoph-Hadas et al, 2001;Friml et al, 2002). In line with these findings, experiments where radiolabeled IAA was applied to woody horizontal shoots of both gymnosperms and angiosperms species have shown that transport is also favored toward the lower side (Leach and Wareing, 1967;Starbuck and Phelps, 1986;Lachaud, 1986). Endogenous levels of IAA were not measured in these experiments, but in the much older stems of pine and poplar used in our study, gravistimulation did not seem to induce any downward redistribution of IAA.…”
Section: Discussionmentioning
confidence: 65%
“…Gravistimulation of primary roots and shoots resulting in differential growth responses and geotropism is mediated by auxin efflux regulators and a lateral transport of IAA toward the lower side in coleoptiles, shoots, and roots as demonstrated in maize coleoptiles, snapdragon, and Arabidopsis (Philippar et al, 1999;Philosoph-Hadas et al, 2001;Friml et al, 2002). In line with these findings, experiments where radiolabeled IAA was applied to woody horizontal shoots of both gymnosperms and angiosperms species have shown that transport is also favored toward the lower side (Leach and Wareing, 1967;Starbuck and Phelps, 1986;Lachaud, 1986). Endogenous levels of IAA were not measured in these experiments, but in the much older stems of pine and poplar used in our study, gravistimulation did not seem to induce any downward redistribution of IAA.…”
Section: Discussionmentioning
confidence: 65%
“…2) The individual cell, as the fundamental unit of all living organisms, can be isolated from tissues and its capability for differentiation investigated in cell suspensions or as protoplasts lacking cell walls (Albinger & Beiderbeck 1983;Reynolds 1987;Church 1993;Leinhos & Savidge 1993). 3) Individual plant tissues can be explanted to defined environmental conditions in attempts to induce or inhibit differentiation (Minocha & Halperin 1976;Liskova 1985;Kutemozinskaet al 1988Kutemozinskaet al , 1991Wilson & Wilson 1991;Savidge 1983bSavidge , 1993bLeitch & Savidge 1995).4) Plant organs, such as stem or root Guttings, have long served as convenient bioassays to investigate xylogenesis (Loomis & Torrey 1964;Torrey & Loomis 1967;Sheriff 1983;Zakrzewski 1983;Gersani 1987;Savidge 1994).5) Finally, development can be investigated in whole plants (Blum 1971;Sharma et al 1979;Starbuck & Phelps 1986;McDaniel et al 1990;Little & Sundberg 1991;Burrows et al 1992;Ma & Steeves 1992;Wang et al 1995). With the increasing technological capability to transform plants genetically, the whole plant bioassay system is becoming an important one for determining the roles of particular genes in controlling morphogenesis (Li et al 1992;Sitbon et al 1992;Halpin et al 1994;Klee & Romano 1994).…”
Section: 'Llysiologymentioning
confidence: 99%
“…A positive correlation was reported between CW formation and accumulation of IAA in cuttings of Douglas fir stems (Starbuck and Roberts, 1983;Starbuck and Phelps, 1986). Sundberg et al (1994) hypothesized that CW formation may be a characteristic of agents effective in blocking the polar transport of endogenous IAA.…”
mentioning
confidence: 97%